2023
DOI: 10.1681/asn.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing AZD5438 and Dabrafenib for Cisplatin-Induced AKI

Chithra K. Pushpan,
Daniel F. Kresock,
Matthew A. Ingersoll
et al.

Abstract: Background: Cisplatin is an effective chemotherapy agent for a wide variety of solid tumors, but its use is dose-limited by serious side effects including acute kidney injury (AKI) and hearing loss. There are no FDA-approved drugs to treat both side effects. Recently, two anti-cancer oral drugs, AZD5438 and dabrafenib, were identified as protective against cisplatin-induced hearing loss in mice. We hypothesize that similar cell stress and death pathways are activated in kidney and inner ear cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
2
1
Order By: Relevance
“…Overactivation of the MAPK pathway, as observed with cisplatin and noise exposure in the inner ear, can lead to downstream cellular stress pathways and eventually to cell death and dysfunction ( Lahne and Gale, 2008 ; Ohori, 2008 ; Cagnol and Chambard, 2010 ; Alagramam et al, 2014 ; Herranen et al, 2018 ; Ingersoll et al, 2020 ). Stimulation of the MAPK pathway has previously been associated with cell survival and proliferation; however, our studies here and previous studies have suggested that this pathway can also act as a cellular stress pathway in some nonproliferating cells such as the inner ear and the kidney ( Jo et al, 2005 ; Ingersoll et al, 2020 , 2023 ; Pushpan et al, 2024 ). Following cisplatin and noise exposure, there is a significant increase in ROS, proinflammatory cytokines and chemokines, and other inflammatory markers, which are all markers of cell stress ( Dhukhwa et al, 2019 ; Ramkumar et al, 2021 ; Al Aameri et al, 2023 ; Wang et al, 2023 ).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Overactivation of the MAPK pathway, as observed with cisplatin and noise exposure in the inner ear, can lead to downstream cellular stress pathways and eventually to cell death and dysfunction ( Lahne and Gale, 2008 ; Ohori, 2008 ; Cagnol and Chambard, 2010 ; Alagramam et al, 2014 ; Herranen et al, 2018 ; Ingersoll et al, 2020 ). Stimulation of the MAPK pathway has previously been associated with cell survival and proliferation; however, our studies here and previous studies have suggested that this pathway can also act as a cellular stress pathway in some nonproliferating cells such as the inner ear and the kidney ( Jo et al, 2005 ; Ingersoll et al, 2020 , 2023 ; Pushpan et al, 2024 ). Following cisplatin and noise exposure, there is a significant increase in ROS, proinflammatory cytokines and chemokines, and other inflammatory markers, which are all markers of cell stress ( Dhukhwa et al, 2019 ; Ramkumar et al, 2021 ; Al Aameri et al, 2023 ; Wang et al, 2023 ).…”
Section: Discussioncontrasting
confidence: 50%
“…Activation of the MAPK pathway as a stress pathway following various damaging stimuli could be a general cell stress pathway that is activated in different postmitotic cells, not just the inner ear cells. Other studies, including ours, have shown that activation of MAPK proteins in other tissues, such as the kidneys and neurons, leads to cellular stress and death ( Jo et al, 2005 ; Ohori, 2008 ; Xu et al, 2016 ; Pucilowska et al, 2018 ; Liu et al, 2022 ; Pushpan et al, 2024 ). This current study contributes further evidence that the MAPK pathway can act as a stress response pathway and targeting the proteins in the pathway could be beneficial for preventing other types of diseases such as acute kidney injury and neuroinflammatory disorders ( Jo et al, 2005 ; Ohori, 2008 ; Cagnol and Chambard, 2010 ; Liu et al, 2022 ; Pushpan et al, 2024 ).…”
Section: Discussionmentioning
confidence: 59%
“…The activation of ERK can also affect immune cell migration, so ERK inhibition could be directly inhibiting the migration of immune cells to the cochlea following noise insult [ 86 , 87 ]. It is interesting to note that ERK inhibitors may also play a key role in sensing damage levels and reducing the immune response in other post-mitotic cells outside the ear, such as in the kidney and neurodegenerative disorders of the joints and brain [ 88 , 89 , 90 ]. Finally, ERK1/2 inhibition has been shown to affect activity-regulated cytoskeleton-associated proteins (Arc) in neurons, which could be another possible mechanism of the protection from hearing loss seen with ERK inhibition [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%